Profile of Microbial Keratitis after Corneal Collagen Cross-Linking. (11th September 2014) - Shetty, Rohit; Kaweri, Luci; Nuijts, Rudy M. M. A.; Nagaraja, Harsha; Arora, Vishal; Kumar, Rajesh S.
Abstract : Purpose . To report the profile of microbial keratitis occurring after corneal collagen cross-linking (CXL) in keratoconus patients. Methods . A retrospective analysis of 2350 patients (1715 conventional CXL, 310 transepithelial CXL, and 325 accelerated CXL) over 7 years (from January 2007 to January 2014) of progressive keratoconus, who underwent CXL at a tertiary eye care centre, was performed. Clinical findings, treatment, and course of disease of four eyes that developed postprocedural moxifloxacin resistant Staphylococcus aureus (MXRSA) infectious keratitis are highlighted. Results . Four eyes that underwent CXL (0.0017%) had corneal infiltrates. All eyes that developed keratitis had conventional CXL. Corneal infiltrates were noted on the third postoperative day. Gram's stain as well as culture reported MXRSA as the causative agent in all cases. Polymerase chain reaction (PCR) in each case was positive for eubacterial genome. All patients were treated with fortified antibiotic eye drops, following which keratitis resolved over a 6-week period with scarring. All these patients were on long-term preoperative oral/topical steroids for chronic disorders (chronic vernal keratoconjunctivitis, bronchial asthma, and chronic eczema). Conclusion . The incidence of infectious keratitis after CXL is a rare complication (0.0017%). MXRSA is a potential organism for causing post-CXL keratitis and should be identified early and treated aggressively with fortified antibiotics.